2013
DOI: 10.1016/j.mssp.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the diameter of silicon nanowires grown using a tin catalyst

Abstract: Silicon nanowires were grown on ITO-coated glass substrates via a pulsed plasma enhanced chemical vapor deposition method, using tin as a catalyst. The thin films of catalyst, with different thicknesses in the range 10-100 nm, were deposited on the substrates by a thermal evaporation method. The effect of the thickness of the thin film catalyst on the morphology of the silicon nanowires was investigated.The scanning/transmission electron microscopy images showed that the wire diameter increased as the thicknes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Thus, the Zn particles aggregated and were larger in diameter than the Au, which in turn led to an increase in the grown wire diameters. For this reason, the density of the grown SiNWs pber unit area is decreased when the diameter of wires increarsed [7].…”
Section: Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the Zn particles aggregated and were larger in diameter than the Au, which in turn led to an increase in the grown wire diameters. For this reason, the density of the grown SiNWs pber unit area is decreased when the diameter of wires increarsed [7].…”
Section: Surface Morphologymentioning
confidence: 99%
“…The choice ofChoosing a suitable catalyst for NW growth depends on the eutectic temperature of the metal-semiconductor system. The properties of the grown SiNWs using the VLS mechanism, such as morphology and crystalinitycrystallinity are affected by the catalyst type and thickness [ 1,[7][8][9]. Increasing thickness of catalyst led to an increase the catalyst droplet diameter and in turn an increase in the diameter of the grown SiNWs.…”
Section: Introductionmentioning
confidence: 99%
“…The surface morphologies of SiNWs synthesized via PPECVD and catalyzed using various thicknesses of Zn are depicted in the FESEM images shown in Figure 1 Al-Taay et al [22,23], who found that using Sn and Al catalysts with varying thickness in the range of 10nm to 100nm led to an increase in the diameter of as-grown SiNWs by PPECVD.…”
Section: Surface Morphologymentioning
confidence: 99%
“…The diffraction peaks of the prepared SiNWs correspond to the because the metal particles were located on top of the SiNWs. Comparing with the SiNWs prepared using Sn and Al catalysts with the same deposition conditions [9,27] , the Au catalyst 7 produced the highest crystallinity SiNWs that makes it the most suitable for solar cell applications.…”
Section: Crystalline Structurementioning
confidence: 99%
“…Furthermore, Qin et al [26] demonstrated that the diameter of SiNWs prepared via inductively coupled PCVD on Si wafers at 380 °C using 16 nm thick Au ranged from 90 nm to 130 nm and increased to 130 nm to 175 nm with a 40 nm thick Au catalyst, in agreement with our results. Al-Taay et al [27] found that the diameter of SiNWs grown by PPECVD using a Sn catalyst also increased as the catalyst thin film thickness increased. The SiNWs were randomly oriented relative to the substrate, and the mean wire length decreased from 12 µm to approximately 10 µm as the thickness of the catalyst film increased from 20 nm to 100 nm.…”
mentioning
confidence: 99%